Bronne vir Jesus-studies - Geyser, P. A. (Hervormde teologiese studies, 1999)
Sources for Jesus studies.The premise of this aricle is that historical research should not be predetermined in any way. All available sources should be utilized. Applied to historical Jesus studies, the implication is that the researcher cannot be restricted to the canon. The article focuses on the sources that are used for histoical Jesus (reconstruction). The Jesus tradition is chronologically stratified according to John Dominic Crossan's, Inventory of the Jesus tradition by chronological stratiication and independent attestation. This inventory is to be found as an appendix to his 1991 book The historical Jesus'. However, the openness to extra-canonical sources does not provide us with any noticeable new information.